EFFICACY AND COST-EFFECTIVENESS, COMPARISON OF 7-DAYS VONOPRAZAN VERSUS 14-DAYS ESOMEPRAZOLE BASED TRIPLE THERAPIES FOR TREATING HELICOBACTER PYLORI INFECTION IN PAKISTANI POPULATION: A RANDOMIZED CLINICAL TRIAL - Farzana Waqar,; Mudassar Noor,; Kulsoom Farhat,; Shabana Ali,; Ehtesham Haider,; Syedah Fauzia Fatima Gillani, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Helicobacter pylori (H. pylori) is a gram-negative bacterium which usually resides in the mucoid lining of the stomach and may cause different gastric pathologies e.g., Gastritis, peptic ulcer disease, adenocarcinoma of the gastric system and mucoid associated lymphoma (MALT). The Objective was to compare the effect of 7-days Vonoprazan based triple therapy and 14-days Esomeprazole based triple therapy on eradication rate, compliance and cost effectiveness in Helicobacter pylori infected patients. Methods: This clinical trial was performed in the Department of Pharmacology Army Medical College, National University of Medical Sciences (NUMS) in collaboration with the Gastroenterology Department, Pak Emirates Military Hospital (PEMH) Rawalpindi from December 2022 to March 2023. A total of one hundred and twenty-two patients with dyspepsia symptoms and yielding lab results positive for Helicobacter pylori by stool antigen test were enrolled in the study. They were randomly allocated into two groups. The Esomeprazole group received 14 days of triple therapy orally with Esomeprazole 20 mg twice a day; Amoxicillin 1000 mg twice a day; and Levofloxacin 500 mg one time a day. The comparative Vonoprazan group was given 7-days triple therapy orally with Vonoprazan 20 mg twice a day; Amoxicillin 1000 mg twice a day; and Levofloxacin 500 mg one time a day. Eradication success was evaluated by stool antigen test four weeks later, as counted from the start of treatment. compliance and cost-effectiveness of both therapies were also assessed. Results: The eradication rate was (95.1%) in the Vonoprazan group with 58 out of 61 patients negative for H. pylori and (93.1%) in Esomeprazole group with 54 patients out of 58 yielding a negative result demonstrating p-value of 0.64. Compliance was 95.0% in the Esomeprazole group with p-value of 0.07. Cost effective ratio for Vonoprazan triple therapy was lower (731.8PKR) than the Esomeprazole group. Conclusion: One two-week Vonoprazan regimen demonstrated improved eradication rate, good compliance, and better tolerability in patients with less cost and a half duration of treatment in comparison with two weeks Esomeprazole regimen, attesting that one week Vonoprazan therapy is more cost efficacious in producing better results.